MOF‐Based Microrobots: MOFBOTS: Metal–Organic‐Framework‐Based Biomedical Microrobots (Adv. Mater. 27/2019). Issue 27 (2nd July 2019) - Wang, Xiaopu; Chen, Xiang‐Zhong; Alcântara, Carlos C. J.; Sevim, Semih; Hoop, Marcus; Terzopoulou, Anastasia; de Marco, Carmela; Hu, Chengzhi; de Mello, Andrew J.; Falcaro, Paolo; Furukawa, Shuhei; Nelson, Bradley J.; et al.
Abstract : Metal–organic frameworks (MOFs) have been recently used as building blocks in micro‐ and nanoswimmers; in article number1901592, Josep Puigmartí‐Luis and co‐workers present 3D soft‐based MOF microrobots that can swim along pre‐designed tracks, achieving both single‐cell targeting in a cell‐culture media and controlled delivery of cargo payloads.